Hypoalbuminemia linked to myocardial dysfunction in recent-onset nephrotic syndrome: a cross-sectional case control 3DSTE study - Antoine AbdelMassih; Mervat Haroun; Mohamed Samir; Samar Younis; Martina Tamer; Amr Salem (SpringerOpen, 2021)
Abstract Background Although myocardial dysfunction in the context of longstanding steroid-resistant nephrotic syndrome (NS) has been the focus of many series, the detection of myocardial involvement in recent-onset NS has not taken sufficient attention. The primary outcome parameter of our study is the detection of myocardial dysfunction in the initial episode of NS (first 4 weeks after the onset), while the secondary outcome parameter is the determination of the best predictor of such dysfunction among systolic blood pressure, diastolic blood pressure, the duration of the initial episode of NS, and biochemical parameters such as serum albumin and cholesterol. Methods Forty NS patients during the initial episode of NS (first 4 weeks from the onset) were examined for anthropometric data as well as for serum albumin and cholesterol. Motion-mode echocardiography was used to determine Fractional shortening, while 3D echocardiography was applied to determine left ventricular (LV) ejection fraction (EF) and GLS (global longitudinal strain). Finally, we employed combined conventional and tissue doppler to determine LV E/e' ratio (ratio of early transmitral inflow and average early diastolic basal septal and mitral annular velocities). Forty healthy, age- and sex-matched controls were enrolled to control advanced echocardiographic parameters. Results LV GLS was markedly reduced in cases compared to controls, denoting subtle systolic dysfunction, while, LV E/e' ratio was significantly higher in cases denoting diastolic dysfunction in early NS. Hypoalbuminemia was found to be the best predictor of both LV GLS and LV E/e' ratio. Conclusion Myocardial dysfunction should be considered in any NS patient even in recent-onset NS, the severity of hypoalbuminemia seems to be the best determinant of this dysfunction either by increasing endothelial dysfunction or through triggering inflammation. Further studies are needed on the mechanism by which hypoalbuminemia induces myocardial dysfunction in NS patients